Tailorable rigidity and energy-absorption capability of 3D printed continuous carbon fiber reinforced polyamide composites. (20th October 2020) - Peng, Yong; Wu, Yiyun; Li, Shixian; Wang, Kui; Yao, Song; Liu, Zhixiang; Garmestani, Hamid
Abstract: The aim of the present work was to study the tailorable rigidity and energy absorption capability of 3D printed short and continuous carbon fiber reinforced polyamide (3DP-scCFRPA). The synergistic reinforcement of laminates by both short and continuous carbon fibers was superior to the individual carbon fiber reinforcement for the mechanical properties. Continuous carbon fiber raster angle, stacking sequence and loading direction were considered as the main factors affecting mechanical properties of 3DP-scCFRPA in this investigation. The flexural strength, modulus and energy absorption capability of 3DP-scCFRPA were investigated by three-point bending testing. The deformation processes and failure mechanisms of laminated composites were analyzed in association with morphological evolution. The results showed that laminates with 0°continuous fiber raster angle (along with the length direction), separated distribution of continuous carbon fiber layers, and loaded in thickness direction, presented the highest flexural modulus and strength as high as 16.1 GPa and 262.0 MPa, respectively. The printed laminates with ± 45° continuous fiber raster angle, separated distribution of continuous carbon fiber reinforced layers, and loaded in width direction showed the highest energy absorption of 1613.3 MJ/mm 3 . Continuous fibers with 0° raster angle could effectively improve rigidity of composites. The introduction of ±45° layers into laminates significantly increased the energy absorption capability of composites. Separated continuous fiber reinforced layers were helpful to impede crack propagation and presented better interfaces with higher interfacial strength between 3D printed layers. Graphical abstract: Image 1